FLOOD INUNDATION ANALYSIS WITH 2-D HEC-RAS MODELLING (CASE STUDY: WAY UMBAN RIVER) - Aprizal, Aprizal; Fitriana, Indri Rahmandhani; Ainistia, Nurul (International Journal of Civil Engineering and Infrastructure, 2024)
The "Way Umban River" is a river that has the potential to cause flooding during the rainy season. Floods are natural disasters that often occur and can cause losses to humans, the environment, and the economy. Flood mitigation helps overcome this problem. Flood modeling analysis is the first step in flood control to identify areas that are vulnerable to flooding. This research analyzes flood modeling using the software HEC-RAS 2-D by unsteady flow type. Three return periods are used, namely 10 years, 25 years, and 50 years. The designed flood discharge is obtained using the HSS Nakayasu method and then used as input in the HEC-RAS model. From the calculation results, the maximum designed flood discharge value for the 10-year return period is 85,03 m3/s, the 25-year return period is 98,30 m3/s, and the 50 years is 108,14 m3/s. Based on 2-D modeling, it is known that the designed discharge value for a return period of 50 years has a wider flood distribution compared to return periods of 10 and 25 years. The ten-year return period flood discharge produces an inundation area of 93,76 ha, the 25-year return period flood discharge produces an area of 98,33 ha, and the 50-year return period flood discharge produces an inundation area of 101,09 ha. Based on the analysis of areas that have the potential to flood, it was found that the locations with the potential to experience inundation are in Tanjungaman Village.